Effect of variations fuel heating on fuel consumption for the Suzuki SJ410 engine - Safriana, Eni; Nailul Ulum, Muhammad Showi; Indrawati, Ragil Tri; Putri, Farika Tono (Politeknik Negeri Semarang, 2023)
AbstractMeans of transportation is one of the needs to make the movement from one place to another. One of the commonly used transportation is motorized vehicles that run on gasoline. Fuel consumption affects the power generated as well as the costs incurred and the time required by motorized vehicles to carry out their functions. This research method uses true experimental design research to conduct performance tests using a Suzuki SJ410 motorized vehicle with an F10A type engine and a capacity of 970 cc. The test was carried out by carrying out the treatment of heating premium fuel through a copper pipe that was installed on the radiator upper tank with a length of 450 mm (MOD 1) and 900 mm (MOD 2) and also under standard conditions (STD). The results obtained stated that fuel consumption under standard conditions (STD) fuel consumption for 26.03 s/50 ml, for a pipe length of 450 mm (MOD 1) for 31.90 s/50 ml and for a pipe length of 900 mm ( MOD 2) for 33.27 s/50 ml.